1992
DOI: 10.3109/00016349209009922
|View full text |Cite
|
Sign up to set email alerts
|

‘Hit and run’ oncogenesis by human papillomavirus type 18 DNA

Abstract: Transfection of an immortalized cell line (AE), derived from Syrian hamster embryo cells, with human papillomavirus type 18 (HPV 18) DNA induced morphological transformation and these transformed cells were tumorigenic in nude mice. Southern blot analysis revealed that the transfected viral DNA was retained in all the cell lines tested, however, all these transformed cells contained only less than one copy per cell of viral genome. Eleven cloned cell lines were established from a tumor cell line obtained after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
(8 reference statements)
0
28
0
1
Order By: Relevance
“…Regarding the role of HPV in LCs, Kinjo et al (2003) has argued that HPV is not aetiologically involved in LC development but that HPV induces squamous metaplasia in ACs. Another possible explanation for such a low viral load may suggest a 'hit-and-run' mechanism, where the virus DNA may be lost after transformation, as shown in studies on a bovine model, and as suggested in HPV-18 oncogenesis and in non-melanoma skin cancer developments mediated by HPV (Iwasaka et al, 1992;Aubin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role of HPV in LCs, Kinjo et al (2003) has argued that HPV is not aetiologically involved in LC development but that HPV induces squamous metaplasia in ACs. Another possible explanation for such a low viral load may suggest a 'hit-and-run' mechanism, where the virus DNA may be lost after transformation, as shown in studies on a bovine model, and as suggested in HPV-18 oncogenesis and in non-melanoma skin cancer developments mediated by HPV (Iwasaka et al, 1992;Aubin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The region 3 0 of the L1 amplicon was extended at least as far as 7244 bp. This suggests that the HPV is fragmented and/or incomplete and may indicate 'hit-and-run' oncogenesis as described for HPV in Syrian hamster embryo cells (Iwasaka et al, 1992) and for human mesothelial cells (De Silva et al, 1994). We are continuing our analysis of the HPV sequence in MBA-MB-175VII and SK-Br-3 cell lines, as well as in two other HPV-containing breast cancer cell lines that are yet to be described and characterised.…”
Section: Sirmentioning
confidence: 98%
“…Subsequently, many examples of hit and run' have been reported, involving notably the herpes viruses, herpes simplex (HSV) McDougall, 1980, 1990;Bauer et al, 1992) and EpsteinBarr (EBV) viruses (Gri n and Karran, 1984;Karran et al, 1990;Yao et al, 1990;Lin et al, 1993;Delecluse et al, 1997;Wolf et al, 1995;Jox et al, 1997;Srinivas et al, 1998, reviewed, Ambinder, 2000, or on occasion cytomegalo (CMV) (Gelb and Dohner, 1984) or varicella zoster (VZV) (Iwasaka et al, 1992) viruses. Shen et al (1997) proposed that`hit and run' transformation by human papilloma (HPV) viruses might be a consequence of mutations induced in cellular genes.…”
Section: Introductioǹmentioning
confidence: 99%